Soy isoflavones induces mitophagy to inhibit the progression of osteosarcoma by blocking the AKT/mTOR signaling pathway - Ziang Zheng; Xinghan Zhao; Bo Yuan; Shan Jiang; Rushan Yan; Xiaowei Dong; Qijun Yao; Haidong Liang (BMC, 2024)
Abstract Background Soy isoflavones (SI) is a natural bioactive substance exhibiting beneficial effects on human health. This study aims to elucidate the therapeutic potential of SI in the treatment of osteosarcoma (OS) and to investigate the underlying mechanisms, particularly focusing on mitophagy. Methods The effects of SI on the proliferation, apoptosis, migration, and invasion of U2OS cells were analyzed. Mitophagy was assessed through multiple parameters: mitochondrial autophagosomes, mitochondrial membrane potential, autophagy-related proteins, reactive oxygen species (ROS), and oxygen consumption rate (OCR). Protein levels related to apoptosis, autophagy, and the AKT/mTOR pathway were analyzed using western blot. The therapeutic efficacy of SI was further identified using a mouse tumor xenograft model. Cell apoptosis and proliferation in tumor xenografts were detected by TUNEL staining and immunohistochemistry (IHC), respectively. Results SI dose-dependently suppressed the viability, colony formation, migration, and invasion of U2OS cells, and enhanced the apoptosis. SI also dose-dependently induced mitophagy in OS cells, evidenced by an increase in autophagosomes and ROS levels, a decrease in mitochondrial membrane potential and OCR, and concomitant changes in autophagy-related proteins. Mdivi-1, an inhibitor of mitophagy, reversed the anti-tumor effects of SI on U2OS cells. In addition, SI blocked the AKT/mTOR pathway in U2OS cells. SC-79, an AKT agonist, reversed the effect of SI on inducing mitophagy. Moreover, SI also promoted cell apoptosis and mitophagy in tumor xenografts in vivo. Conclusions SI induces mitophagy in OS cells by blocking the AKT/mTOR pathway, contributing to the inhibition of OS.